Non-receptor tyrosine kinase inhibitors enhances beta-cell survival by suppressing the PKC delta signal transduction pathway in streptozotocin - induced beta-cell apoptosis - Karunakaran, Udayakumar; Park, Si Jun; Jun, Do Youn; Sim, Taebo; Park, Keun-Gyu; Kim, Myoung Ok; Lee, In Kyu (ELSEVIER SCIENCE INC, 2015)
GNF-2 and GNF-5 are members of a new class of non-receptor tyrosine kinases inhibitors that possess excellent selectivity towards imatinib-resistant mutations found in chronic myeloid leukemia patients. On the other hand recent reports implicate abnormal tyrosine kinase signaling in beta-cell death in Type I and Type II diabetes. In this work we determined the effects of GNF-2, GNF-5 on pancreatic beta-cell death caused by streptozotocin (STZ). STZ treatment causes apoptosis of INS-1 cells by activation of intracellular ROS, c-jun N-terminal kinase (JNK), caspase 3, and caspase 3-dependent activation of protein kinase C delta (PKC delta). GNF-2 and GNF-5 increased cell viability and attenuated STZ-induced intracellular ROS and significantly reduced the activation of JNK, caspase 3, and caspase 3-dependent activation of PKC delta. In studies with intact mice, GFN-2 and GNF-5 prevented the loss of beta cells and the increase in blood glucose produced by STZ-treated control mice. Furthermore, immunohistochemical analysis revealed that GNF-2 and GNF-5 increased insulin protein levels in STZ-treated mice when compared with control mice. These findings suggest that non-receptor tyrosine kinase inhibitors provide a new approach for the treatment of new-onset Type land Type II diabetes. (C) 2015 Elsevier Inc. All rights reserved.